KARAKTERISTIK JELLY DRINK SINBIOTIK DARI SUSU KEDELAI DAN EKSTRAK BUAH NAGA MERAH (Hylocereus polyrhizus) - Sri Winarti; Ulya Sarofa; Koyi Fatkul Rodiyah (AGROINTEK, 2018)
Jelly drink is a gel-based beverage product, which can be made from hydrocolloid compounds by addition of sugars, acids, and or without other food additives, sinbiotics are a combination of probiotics and prebiotics. The purpose of this study was to determine the effect concentration of carrageenan and fermentation timt on the quality of jelly drink sinbiotik soy milk and red dragon fruit extract. The method used in this research is Completely Randomized Design with two factors. The first factor was the concentration of carrageenan (0.4%, 0.6%, 0.8%) and the second factor of fermentation time (18 hours, 20 hours, 22 hours and 24 hours). To know the difference between treatments used Duncan Multiple Range Test (DMRT 5%). The results showed that the best treatment was the addition of carrageenan 0,8% and the  fermentation time of 24 hours which resulted jelly drink sinbiotik with pH value 3,7, total acid 1,02%, total lactic acid bacteria (BAL) 11,13 log cfu/ml, total sugar 7.92%, 1.89% dissolved protein, total anthocyanin 0.645% and gel strength 3.27 N.